Diversity Analysis of Weed Flora in Spring Rice Fields of Saptari District, Nepal - Bhujel, Alisha; Pradhan, Ankita; Rijal, Purnima; Paudel, Shrisha; Pantha, Aishwarya; Tiwari, Manila; Timilsina, Umesh; Shrestha, Abhishek (Agronomy Journal of Nepal, 2025)
Grown in a variety of environments, including irrigated lowlands and uplands, rice is a major crop in Nepal. Drought, flooding, and weeds are just a few of the difficulties farmers confront that can drastically lower harvests. Although improved spring rice types are being used more frequently to address these problems, weeds are still a major issue. Using 22 quadrats per stage, this study examined weeds in spring rice fields in Saptari, Eastern Terai, at three crucial growth stages: tillering, milking, and maturity. The milking stage had the maximum weed abundance (2,492), followed by tillering (2,337) and maturity (753). Cyperus difformis, Eclipta prostrata, Fimbristylis littoralis, Alternanthera sessilis, and Monochoria vaginalis were the most prevalent species. Grasses were scarce, broad-leaved weeds predominated, and the most prevalent groups were Cyperaceae, Asteraceae, Poaceae, and Amaranthaceae. Diversity peaked at the maturity stage, indicating changes in the makeup of weeds as the crop grows. These results demonstrate that weed biology, rice development, and environmental factors all affect weed variety and abundance. By identifying these trends, farmers in the Eastern Terai can improve spring rice productivity by creating integrated weed management plans that are specific to the region.